PERAN KURIKULUM MERDEKA DALAM PENGEMBANGAN LITERASI DIGITAL DAN KARAKTER PESERTA DIDIK - Slamet; Fitri Puji Rahmawati; Anik Gufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze how the implementation of the Merdeka Curriculum can enhance students' digital literacy skills and foster strong and positive character development. The research employs a literature review method to examine the role of the Merdeka Curriculum in developing digital literacy and student character. Literature review is a research method designed to collect, review, and analyze data or information from various sources, such as journals, books, articles, research reports, and other relevant documents. The study indicates that the implementation of the Merdeka Curriculum positively contributes to optimizing digital literacy and character development among students. The use of New Media Theory highlights that digital literacy is an essential skill that students must master in the digital age. The Merdeka Curriculum effectively accommodates the ongoing advancements in information and communication technology, enabling students to keep pace with global developments.